2016
DOI: 10.1111/exsy.12187
|View full text |Cite
|
Sign up to set email alerts
|

Setting accessibility preferences about learning objects within adaptive elearning systems: User experience and organizational aspects

Abstract: Higher and further education providers are facing the challenge of supporting the interaction needs of an increasing number of students who feature accessibility preferences to use both elearning contents and services. In the next future, we can expect that, within adaptive elearning systems, both automatic and manual procedures will interoperate to elicit users' interaction needs for ensuring accessibility. In this paper, we report findings from the user experience with the self‐assessment of interaction need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…The existing relevant studies have sufficiently explained the general concepts of accessibility, disability, diversity, universal access as well as the demographics [22][23][24][25][26][27]29,30,33,35,38,[42][43][44]46,54,56,57,60,61]. In the same way, the Convention of the Rights of Persons with Disabilities [29,44,59] and related legislation had also been addressed, both in general [29,44,61] and countryspecific level, e.g.…”
Section: Moocs and The Characterization Of The Accessibility Problemmentioning
confidence: 99%
“…The existing relevant studies have sufficiently explained the general concepts of accessibility, disability, diversity, universal access as well as the demographics [22][23][24][25][26][27]29,30,33,35,38,[42][43][44]46,54,56,57,60,61]. In the same way, the Convention of the Rights of Persons with Disabilities [29,44,59] and related legislation had also been addressed, both in general [29,44,61] and countryspecific level, e.g.…”
Section: Moocs and The Characterization Of The Accessibility Problemmentioning
confidence: 99%
“…Unlike other AI models, the Chatbot is constantly interacting with students and obtaining information from them. Therefore, the development of, in addition to recommending activities, seeks to learn from each student by identifying their needs directly [27].…”
Section: Variable Identificationmentioning
confidence: 99%
“…The most common models of AI are expert systems, recognition systems, behavior-based intelligence, etc. Ideally, it should focus on a type of model that fits the needs of the students and whose interaction contributes to the motivation of the students [27]. One of the tools that most enhances the handling and interaction with users is the Chatbot.…”
Section: Model Of a Chatbot With The Use Of Artificial Intelligencementioning
confidence: 99%
“…Aspects" (Rodriguez-Ascaso, Boticario, Finat, & Petrie, 2017), where the authors have reported the experience acquired by students as users of a content personalization systems, which tackles possible mismatches in the interaction between the user and the learning objects. This work concludes that the selected approach permit students to report their…”
Section: "Automatic Estimation Of Difficulty Level Of Exercises In a mentioning
confidence: 99%
“…Another key aspect of artificial intelligence (AI) in education is accessibility. In this respect, content personalization is in the focus of the paper “Setting Accessibility Preferences About Learning Objects Within Adaptive elearning Systems: User Experience and Organizational Aspects” (Rodriguez‐Ascaso, Boticario, Finat, & Petrie, ), where the authors have reported the experience acquired by students as users of a content personalization systems, which tackles possible mismatches in the interaction between the user and the learning objects. This work concludes that the selected approach permit students to report their interaction preferences and open the issue of how to solve different accessibility needs in massive online courses.…”
mentioning
confidence: 99%